2015
DOI: 10.1093/ntr/ntv237
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Electronic Cigarette Use Among Adults in the United States

Abstract: Data from 2014 National Health Interview Survey indicate that e-cigarettes have not been attracting adult non-smokers or promoting relapse in longer term former smokers. Moreover, the data are suggestive that some recent quitters may have done so with the assistance of e-cigarettes. Creating measures of smoking status that treat former smokers as a homogenous group is insufficient to assess the epidemiology of e-cigarette use and the potential impact on public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
210
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(237 citation statements)
references
References 20 publications
21
210
6
Order By: Relevance
“…A growing body of evidence supports dual tobacco‐product use as the most prevalent tobacco‐use pattern 18, 19, 20. In line with our findings, the PATH (Population Assessment of Tobacco and Health) study, the CDC, and the NHIS (National Health Interview Survey) have indicated that e‐cigarette users are more likely to be current or former smokers 18, 19, 20. The high prevalence of e‐cigarette use among current smokers should be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports dual tobacco‐product use as the most prevalent tobacco‐use pattern 18, 19, 20. In line with our findings, the PATH (Population Assessment of Tobacco and Health) study, the CDC, and the NHIS (National Health Interview Survey) have indicated that e‐cigarette users are more likely to be current or former smokers 18, 19, 20. The high prevalence of e‐cigarette use among current smokers should be interpreted carefully.…”
Section: Discussionmentioning
confidence: 99%
“…44 Use is more common in younger adults; 21.6% of people 18 -24 y old have tried e-cigarettes versus 3.7% of people Ͼ65 y old. 3 Individuals who report recently quitting tobacco are significantly more likely to report active use of e-cigarettes, with 22% of recent quitters reporting use versus 3.7% of all adults.…”
Section: Epidemiologymentioning
confidence: 99%
“…3 Individuals who report recently quitting tobacco are significantly more likely to report active use of e-cigarettes, with 22% of recent quitters reporting use versus 3.7% of all adults. 44 Overall, use of e-cigarettes by adults is primarily limited to smokers and recent former smokers, with only 0.4% of never smokers and 0.8% of smokers quitting Ͼ4 y prior reporting e-cigarette use. 44 E-cigarette use appears to be increasing among in young adults.…”
Section: Epidemiologymentioning
confidence: 99%
“…Since vape shops predominantly sell ENDS, we might expect their customers to be similar to ENDS users. In a 2014 national sample of adults, ever use of e-cigarettes was correlated with daily cigarette smoking, White race, younger age (age [18][19][20][21][22][23][24], and living in the Western U.S 7 . One study noted an increase in lifetime e-cigarette use in young adults (aged 18-24) since 2010, 8 but another showed that ever e-cigarette use remained stable in this age group 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent national study found that young adults (18)(19)(20)(21)(22)(23)(24) were more likely to be some day or every day e-cigarette users than were adults over age 45. 7 Young adult past 30-day e-cigarette users compared with those with no past-month use have also reported higher prevalence of marijuana use (some days or ever day 10 or in the past 12 months 11 ), some days or every day alcohol use, 10 past 30-day binge drinking, 11 and past 30-day other tobacco (defined as use of cigars, pipes, chewing tobacco, snuff, snus, hookah, clove cigarettes, bidis, or other) product use 11 . This pattern of e-cigarette co-use with a variety of other substances may indicate a common liability to use addictive substances based on genetic, neurochemical, physiological, behavioral, and/ or environmental factors [12][13] .…”
Section: Introductionmentioning
confidence: 99%